The Role of Tafsir Tarbawi in the Development of Islamic Personality in Early Childhood - Nanih Nurhayati; Iskandar Mirza (al-Afkar, Journal For Islamic Studies, 2025)
Tarbawi interpretation is an interpretation approach that prioritizes moral and spiritual development through understanding the Koran. This interpretation not only explains the meaning of the verses of the Koran textually, but also highlights educational values that can be applied in everyday life, especially in educating children. Research concludes that Tafsir Tarbawi has an important role in early childhood education, especially in shaping Islamic personalities. Through the interpretation of verses from the Koran that focus on educational aspects, children can learn about essential moral and spiritual values, such as monotheism, noble morals, equality, good social relationships, and emotional intelligence.